2022
DOI: 10.3390/jcm11113163
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Withdrawn vs. Agitated Relatives during Resuscitation on Team Workload: A Single-Center Randomised Simulation-Based Study

Abstract: Background: Guidelines recommend that relatives be present during cardiopulmonary resuscitation (CPR). This randomised trial investigated the effects of two different behaviour patterns of relatives on rescuers’ perceived stress and quality of CPR. Material and methods: Teams of three to four physicians were randomised to perform CPR in the presence of no relatives (control group), a withdrawn relative, or an agitated relative, played by actors according to a scripted role, and to three different models of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One recent randomized simulation-based study demonstrated that interaction with a family member accounted for up to 25% of resuscitation time. 37,38 While the presence of family members increased frustration, it did not affect hands-on time 37 and family presence had no negative effect on the quality of CPR. 38 However, CPR prolongation does not necessarily need to have a negative impact on the outcome of the patient.…”
Section: Discussionmentioning
confidence: 94%
“…One recent randomized simulation-based study demonstrated that interaction with a family member accounted for up to 25% of resuscitation time. 37,38 While the presence of family members increased frustration, it did not affect hands-on time 37 and family presence had no negative effect on the quality of CPR. 38 However, CPR prolongation does not necessarily need to have a negative impact on the outcome of the patient.…”
Section: Discussionmentioning
confidence: 94%
“…This is a prospective comparative trial of two cohorts: during the pandemic years 2020 and 2021, all participants of our workshops performed CPR with PPE (PPE group), while a cohort of participants of pre-pandemic workshops of 2016 to 2019 [ 23 , 24 , 25 ] served as the control group. Apart from the need to wear PPE, the conditions and settings for both cohorts were identical.…”
Section: Methodsmentioning
confidence: 99%